Spectral riometer observation of atmospheric iononization due to energetic electron precipitation - Tanaka, Yoshimasa; Antti, Kero; Nishimura, Koji; Kataoka, Ryuho; Ogawa, Yasunobu; Nishiyama, Takanori; Kadokura, Akira; Yukimatu, Akira; Yamagishi, Hisao; Miyoshi, Yoshizumi; Ozaki, Mitsunori; Tsuchiya, Fuminori; et al. (2019)
The Tenth Symposium on Polar Science/Special session: [S] Future plan of Antarctic research: Towards phase X of the Japanese Antarctic Research Project (2022-2028) and beyond, Tue. 3 Dec. / Entrance Hall (1st floor) at National Institute of Polar Research (NIPR) conference object